al-Ta’āysy al-Ṡaqāfī wa al-Ḥaḍārī bi al-Magrib - Youssef Ben-Naouar (Aphorisme: Journal of Arabic Language, Literature, and Education, 2021)
This study aims to describe the culture and civilization in Morocco in the context of sociology. This research method is qualitative-descriptive. The research data were obtained from literature that describes the culture and civilization of the Moroccan state. The data collection technique is done with documentation. Meanwhile, data analysis was carried out by data reduction, data classification, and data interpretation. The results of the study found that the existence of civilization and culture in Morocco cannot be separated from the social, linguistic and religious context. In a social context, for example, Morocco has various kinds of cultures. This is motivated by the existence of heterogeneous tribes and communities. In the context of language, Morocco uses Arabic as the national language, but many people adopt Arabic 'Amiyah in their speech acts. Then in the context of religion, several religions in Morocco are found, such as Islam, Judaism, Christianity, and other religions.